The industrialization of potatoes and the socioeconomic development of family farming in Lima, Peru - Cervantes, D. M.; Quevedo, J. M. (Peruvian Agricultural Research, 2020)
Objectives: To analyze the factors that influence the industrialization of the potato and its role as an innovation for the socioeconomic development of small family farming in Lima, Peru. Methodology: This study is based on different information sources from public organizations in Peru to show that the industrialization of potatoes in Lima, Peru contributes to the socioeconomic development of family farming. On this basis, recommendations are made for a business model through cooperatives oriented mainly to family farming. Results: The determining factors that influence the industrialization of potatoes in Lima are, the use of certified seed and varieties suitable for processing, compliance with good agricultural practices in potato farms and the permissible limits of presence of agrochemicals in the tuber, the adaptation to the normative framework of DL 1062 Food Safety Law, allowing to enter a market that demands food with sanitary guarantee, which can be achieved through a cooperative organization of farmers. Conclusions: The industrialization of potatoes constitutes a business opportunity to increase the supply of processed potatoes through cooperatives, generating added value for small fresh potato producers in Lima.